A multi‐biomarker study on Atlantic salmon (Salmo salar L.) affected by the emerging Red Skin Disease in the Baltic Sea. Issue 4 (26th October 2020) - Weichert, Fabian G.; Axén, Charlotte; Förlin, Lars; Inostroza, Pedro A.; Kammann, Ulrike; Welling, Annikki; Sturve, Joachim; Asker, Noomi
Abstract: For half a decade, the Atlantic salmon in the Baltic Sea has been facing severe health issues. Clinical signs like haemorrhage, erosions and ulcerative/necrotic skin conditions in returning adults have been reported from different Swedish rivers. These primary disease signs precede a secondary, terminal fungal infection. As initial investigations of the disease did not provide conclusive answers regarding the pathogenesis, this study was initiated to gain insight into a possible link between this so‐called Red Skin Disease and anthropogenic influences. Therefore, returning salmon were caught in rivers along the Swedish coast and different tissues were sampled. The focus was put on the measurements of a battery of biomarkers as well as biochemical and haematological parameters, which were analysed using multivariate statistics. The main findings were a severe osmotic haemodilution, an immune response and an alteration of the carbohydrate metabolism in diseased fish. Furthermore, oxidative stress does not seem to be a likely factor in the pathogenesis. Concluding, certain changes in physiological parameters were shown to be indicative for the disease patterns, while others were ruled out as significant factors. Thus, this study contributes to the understanding of the Red Skin Disease and may act as a hypothesis generator for future studies.